PROSES BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN MASALAH BANGUN RUANG BERDASARKAN TAHAPAN WALLAS DI SMP - Amalia, Anissa; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to describe the students creative thinking process in geometry problem solving based on wallas stage to the ninth-grade students of SMPN 03 Pontianak observed from their mathematic ability. This research used descriptive study case method. The subject in this research were 6 student of by  IX A and IX E class. Method of data collection were taken by written a test to discover the creative thinking process based on wallas stage; final mathematic score in even semester to know student’s mathematic ability; and did some interview to knows student’s creative thinking process deeply. The result of this research show that  student in IX A are R1 who has high ability  and R3  who has low ability; and student in IX E is R2  who has intermediate ability. Then, the result indicate that creative thinking process involved stage which include synthesis ideas with their own word, planning to apply the ideas in many ways, solving their palanning and looking back their answer. The analysis also show every wallas stage of creative thingking proces is distinct each student. The interest thing is R3 could passed the wallas stage very well than two other. Keywords: Creative Thinking Process, Geometry Problem Solving, Wallas Stage